2014
DOI: 10.4103/2231-4040.126985
|View full text |Cite
|
Sign up to set email alerts
|

A validated stability-indicating liquid chromatographic method for determination of process related impurities and degradation behavior of Irbesartan in solid oral dosage

Abstract: The present work describes the development and validation of a stability-indicating RP-HPLC method for the estimation of degradation and process related impurities of Irbesartan, namely Impurity-1, Impurity-2, Impurity-3 and Impurity-4. The developed LC method was validated with respect to specificity, limit of detection and quantification, linearity, precision, accuracy and robustness. The chromatographic separation was achieved on Hypersil Octadecylsilyl (4.6 mm × 150 mm, 3 μm) column by using mobile phase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…and chronic kidney failure . (Weber , 1997), A survey of the literature revealed that several methods have been used to estimate IRBN both purely and in pharmaceutical preparations, directly or indirectly for IRBN, and they include: spectrophotometric methods (Biyani and Yadav, 2019) , (Khalid et al , 2017) , (Jadhav et al , 2014) and (Syeda et al ,2011 ) , HPLC (Alanazi et al , 2014) , (Koyuturk et al , 2014) , (Goswami , 2014) and (Vujić et al , 2012), LC-MS (Qui et al , 2014) and( Chi andChia 2011). The primary objective of the current review was to improve a rational, rapid and modest method for testing irbesartan in its pharmaceutical preparations for routine quality control examination, given spectroscopic analysis, furthermore the procedure has been effectively applied for assurance of IRBN in tablets.…”
Section: Introductionmentioning
confidence: 99%
“…and chronic kidney failure . (Weber , 1997), A survey of the literature revealed that several methods have been used to estimate IRBN both purely and in pharmaceutical preparations, directly or indirectly for IRBN, and they include: spectrophotometric methods (Biyani and Yadav, 2019) , (Khalid et al , 2017) , (Jadhav et al , 2014) and (Syeda et al ,2011 ) , HPLC (Alanazi et al , 2014) , (Koyuturk et al , 2014) , (Goswami , 2014) and (Vujić et al , 2012), LC-MS (Qui et al , 2014) and( Chi andChia 2011). The primary objective of the current review was to improve a rational, rapid and modest method for testing irbesartan in its pharmaceutical preparations for routine quality control examination, given spectroscopic analysis, furthermore the procedure has been effectively applied for assurance of IRBN in tablets.…”
Section: Introductionmentioning
confidence: 99%
“…The drug is official in BP [3] and USP [4], which describe HPLC methods for the assay of irbesartan. Few methods have been described for the determination of irbesartan in pharmaceutical dosage forms by HPLC [28][29][30][31][32], extractive spectrophotometry with Picric acid, bromocresol green, bromothymol blue, cobalt thiocyanate and molybdenum (V) thiocyanate [33], spectrophotometry [34][35][36] and HPTLC [37]. Several HPLC [38][39][40][41][42][43][44][45], spectrophotometry [44][45][46][47][48][49][50] and capillary electrophoresis methods [51,52] are reported in the literature for the determination of irbesartan in combined pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 99%